Lembaga Pengawas Syariah Dalam Sorotan - Yovenska L.Man (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Abstract: Islamic financial institutions are currently considered quite significant. However, on the other hand, of course, everything is not free from some shortcomings that should be a concern. Among those questioned, among others, is the role of the Sharia Supervisory Board in terms of implementing Good Corporate Governance (GCG). This paper will focus on discussions regarding planning and implementing strategies towards the Ideal Sharia Supervisory Board